Comparative Analysis of Roman-Persian Political and Economic Periods with Contemporary in Islamic Perspectives - Romadhan, Raid Azhar; Zakaria, Achmad; Rifki, Muhamad; Mashudi (Fakultas Ilmu Sosial dan Ilmu Politik (FISIP) UIN Walisongo, 2025)
This study investigates the comparative dynamics of economic politics during the Roman-Persian period and the contemporary era through the lens of Islamic economic principles. It explores key dimensions such as resource management, wealth distribution, and the societal impact of policy, particularly in relation to social inequality, resource exploitation, and moral degradation. Employing a qualitative methodology based on an extensive literature review of secondary sources, this research reveals that while the Roman-Persian political economy succeeded in maintaining imperial stability, it also perpetuated significant social disparities through excessive taxation and territorial exploitation. In contrast, the modern economic paradigm, driven by technological innovation and global integration, remains susceptible to systemic crises and widening inequities. The findings suggest that core Islamic tenets—namely zakat, the prohibition of usury (riba), and equitable wealth distribution—offer a normative framework for constructing a more just and resilient economic order, both historically and in contemporary contexts.